In-Lake Processes Offset Increased Terrestrial Inputs of Dissolved Organic Carbon and Color to Lakes - Köhler, Stephan J. (Public Library of Science, 2013)
Increased color in surface waters, or browning, can alter lake ecological function, lake thermal stratification and pose difficulties for drinking water treatment. Mechanisms suggested to cause browning include increased dissolved organic carbon (DOC) and iron concentrations, as well as a shift to more colored DOC. While browning of surface waters is widespread and well documented, little is known about why some lakes resist it. Here, we present a comprehensive study of Mälaren, the third largest lake in Sweden. In Mälaren, the vast majority of water and DOC enters a western lake basin, and after approximately 2.8 years, drains from an eastern basin. Despite 40 years of increased terrestrial inputs of colored substances to western lake basins, the eastern basin has resisted browning over this time period. Here we find the half-life of iron was far shorter (0.6 years) than colored organic matter (A(420) ; 1.7 years) and DOC as a whole (6.1 years). We found changes in filtered iron concentrations relate strongly to the observed loss of color in the western basins. In addition, we observed a substantial shift from colored DOC of terrestrial origin, to less colored autochthonous sources, with a substantial decrease in aromaticity (-17%) across the lake. We suggest that rapid losses of iron and colored DOC caused the limited browning observed in eastern lake basins. Across a wider dataset of 69 Swedish lakes, we observed greatest browning in acidic lakes with shorter retention times (< 1.5 years). These findings suggest that water residence time, along with iron, pH and colored DOC may be of central importance when modeling and projecting changes in brownification on broader spatial scales.